Heterogeneous Agglomeration - Faggio, Giulia; Silva, Olmo; Strange, William C. (The Review of Economics and Statistics, 2017)
Many prior treatments of agglomeration explicitly or implicitly assume that all industries agglomerate for the same reasons. This paper uses U.K. establishment-level coagglomeration data to document substantial heterogeneity across industries in the microfoundations of agglomeration economies. It finds robust evidence of organizational and adaptive agglomeration forces as discussed by Chinitz (1961), Vernon (1960), and Jacobs (1969). These forces interact with the traditional Marshallian (1890) factors of input sharing, labor pooling, and knowledge spillovers, establishing a previously unrecognized complementarity between the approaches of Marshall and Jacobs, as well as others, to the analysis of agglomeration.